Design of Web-Based Futsal Field Rental Accounting Information System in Village-Owned Enterprises - Hery Dwi Yulianto; Lilis Puspitawati; Raiswati Untsa Mega (AFRE (Accounting and Financial Review), 2021)
The purpose of this research is to facilitate village-owned enterprises in developing newly initiated businesses, one of which is the rental of a futsal field. From the business process built, members, plan to accelerate the system by utilizing information system technology and comply with financial accounting standards for micro, small, and medium enterprises. To support the manufacture of this system, the method used is the prototype method with the stages of communication, planning, modelling, development, and deployment. Based on the research results by futsal field operators, the level of accounting knowledge is still low, especially accounting knowledge for micro, small and medium entities. To assist and facilitate operators in making financial reports according to standards, the development of a web-based futsal field rental application helps accelerate the business processes of Village-Owned Enterprises, digitally documenting processes, and making financial reports according to financial accounting standards for micro, small and medium enterprises.DOI: https://doi.org/10.26905/afr.v4i2.5995